ASBABUN NUZUL: KONSEP DAN RELEVANSINYA DALAM MEMAHAMI AL-QURAN - Muh. Samsunar; Nasrullah Bin Sapa; Halima Basri (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
The backdrop or circumstances that preceded the revelation of a Qur'anic verse are referred to as Asbabun Nuzul. Since it gives the social, political, and cultural background for the Qur'anic verses, understanding this idea is crucial to understanding them. One efficient method for thoroughly exploring and comprehending subjects, particularly those pertaining to the study of concepts like Asbabun Nuzul, is to employ a qualitative research approach employing the library research method. The study's findings demonstrate that both classical and modern academics value the idea of Asbabun Nuzul, which explains the rationale for the Qur'anic verses' revelation. Classical scholars like Ibn Kathir and Al- Tabari stress how crucial it is to comprehend the historical background in order to correctly interpret the scriptures. Sayyid Qutb and Fazlur Rahman, two modern scholars, agree that Asbabun Nuzul is significant, but they also stress that the lessons of the Qur'an are still applicable in today's world. All things considered, Asbabun Nuzul aids in accurately and practically comprehending passages in both historical and modern situations.